Investigating antibacterial and anti-inflammatory properties of synthetic curcuminoids - Veselá, Kateřina; Kejík, Zdeněk; Abramenko, Nikita; Kaplánek, Robert; Jakubek, Milan; Petrlova, Jitka (Frontiers in Medicine, 2024)
The concept of intratumoral microbiota is gaining attention in current research. Tumorassociated microbiota can activate oncogenic signaling pathways such as NF-κB, thereby promoting tumor development and progression. Numerous studies have demonstrated that curcumin and its analogs possess strong antitumor effects by targeting the NF-κB signaling pathway, along with potent antibacterial properties. In this study, we tested the antibacterial activity of two curcuminoids, Py-cPen and V-cPen, against the Gram-negative bacterial strains Pseudomonas aeruginosa and Escherichia coli, as well as the Gram-positive bacterial strain Streptococcus aureus using in vitro assays and fluorescent microscopy. We also observed that both Py-cPen and V-cPen reduced NF-κB activation upon lipopolysaccharide (LPS) challenge in cell assays. Additionally, our findings indicate that Py-cPen and V-cPen interact with LPS, as demonstrated by transmission electron microscopy and confirmed by in silico analyses, thereby modulating LPS activity. Overall, our data indicate that Py-cPen and V-cPen exhibit strong antibacterial and anti-inflammatory properties, suggesting their potential as candidates for new multitarget therapeutic strategies.